PENINGKATAN KEMAMPUAN MAHASISWA DALAM BERBICARA BAHASA ARAB DI MA’HAD AL-JAMI’AH UIN AR-RANIRY - abizar abizar (Islam Futura, 2017)
The aim of this research is to know the various programs of Ma’had Al-Jami’ah and its implementation as well as to know the learning result of the students of UIN Ar- Raniry whether before and after implementation of those various programs. The method used in this research was descriptive- analysis. The researcher also used random sampling with 454 samples that consist of three batches. The instrument used in collecting data is direct observation, interview, documents analysis, and test. The finding of this research as follows: the implementation of those various program of Ma’had Al-Jami’ah UIN Ar-Raniry could increase the students’ ability in speaking and beneficial also very helpful for them to increase their ability in speaking. In addition, those programs have significant role in order to increase their ability in speaking, it was suited with their pre test and post test analyzed by the researcher. The students who passed in pre test was 63% and failed was 37%, while students who passed in post test was 88% and failed was 12%.